DESIGN OF ORGANIC WASTE PROCESSING EQUIPMENT FOR LIQUID SMOKE PRODUCTION (Journal of Renewable Energy and Mechanics, 2025)
This study presents the design of an organic waste processing device to produce liquid smoke through combustion, particle separation, and condensation processes. The system consists of a combustion chamber, a cyclone separator, and a condensation tube, which were designed and analyzed numerically with software. Dry organic waste such as coconut shells, rice husks, and leaves was used as raw material with a capacity of 15 kg per cycle. Simulation results show that the combustion chamber reached a maximum temperature of approximately 333°C, the cyclone separator achieved flow velocities of 4.72–7.48 m/s with effective particle separation, and the condensation tube reduced the smoke temperature to around 27°C, enabling liquid smoke formation. This device offers potential as a solution for organic waste management while producing valuable by-products such as natural pesticides and organic preservatives.